Potential Herb-Drug Interactions in the Management of Age-Related Cognitive Dysfunction - Maria D. Auxtero; Susana Chalante; Mário R. Abade; Rui Jorge; Ana I. Fernandes (MDPI AG, 2021)
Late-life mild cognitive impairment and dementia represent a significant burden on healthcare systems and a unique challenge to medicine due to the currently limited treatment options. Plant phytochemicals have been considered in alternative, or complementary, prevention and treatment strategies. Herbals are consumed as such, or as food supplements, whose consumption has recently increased. However, these products are not exempt from adverse effects and pharmacological interactions, presenting a special risk in aged, polymedicated individuals. Understanding pharmacokinetic and pharmacodynamic interactions is warranted to avoid undesirable adverse drug reactions, which may result in unwanted side-effects or therapeutic failure. The present study reviews the potential interactions between selected bioactive compounds (170) used by seniors for cognitive enhancement and representative drugs of 10 pharmacotherapeutic classes commonly prescribed to the middle-aged adults, often multimorbid and polymedicated, to anticipate and prevent risks arising from their co-administration. A literature review was conducted to identify mutual targets affected (inhibition/induction/substrate), the frequency of which was taken as a measure of potential interaction. Although a limited number of drugs were studied, from this work, interaction with other drugs affecting the same targets may be anticipated and prevented, constituting a valuable tool for healthcare professionals in clinical practice.